PWE-070 Initial experience of thiopurine metabolite measurements in the management of ibd in edinburgh. (22nd June 2015) - Singh, P; Noble, CL; Shand, AG; Arnott, ID; Lees, CW; Satsangi, J; Kennedy, NA
Abstract : Introduction: Thiopurine metabolites 6-thioguanine nucleotides (6TGN) and 6-methylmercaptopurine (6MMPN) are end products of thiopurine metabolism which are linked to thiopurine efficacy and increased risk of hepatotoxicity respectively. Variation in metabolism amongst individuals leads to differences in metabolite levels among patients. Thiopurine metabolite testing is used as a tool to guide thiopurine dosing based on metabolite concentrations with the aim of improving disease control and reducing drug related toxicity. 1 Method: Patients within NHS Lothian who had thiopurine metabolite tests for IBD between January 2011 and February 2013 were identified. Electronic patient records and case notes were reviewed retrospectively to determine metabolite test indication, changes to therapy post-metabolite testing and subsequent clinical outcomes. An improvement in outcome encompassed improved disease control, improved adherence, reduced adverse drug effects and a decision to escalate to other therapies where this was motivated by knowledge of adequate 6TGN concentration. Results: 159 patients who had thiopurine metabolite testing were studied after 44 exclusions. Test indication was lack of efficacy in 117 patients (73.6%), adverse effects in 6 (3.8%), combination of inefficacy and adverse effects in 3 (1.9%) and routine monitoring in 33 (22.8%). Fifty-eight (49.6%) of those tested for inefficacy, 3 (50.0%) in the adverse reaction group and 3 (10.7%) who were routinely monitored showed improved clinical outcomes related to their testing. Addition of allopurinol in 13 patients who were deemed thiopurine shunters led to marked increased in 6TGN concentrations and reduction in those of 6MMPN. Conclusion: Thiopurine metabolite testing is of significant clinical benefit in patients showing inefficacious response to thiopurines and those with low 6TGN concentrations. It is also useful in detecting non-adherence to therapy. Thiopurine and allopurinol co-therapy results in marked increase in 6TGN concentrations and improved patient outcomes. This study does not show clear benefits for routine testing of metabolites. Disclosure of interest: None Declared. References: Gearry RB, Barclay ML. Azathioprine and 6-mercaptopurine pharmacogenetics and metabolite monitoring in inflammatory bowel disease. J Gastroenterol Hepatol . 2005;20(8):1149–57 Sparrow MP, Hande SA, Friedman S, Cao D, Hanauer SB. Effect of allopurinol on clinical outcomes in inflammatory bowel disease nonresponders to azathioprine or 6-mercaptopurine. Clin Gastroenterol Hepatol . 2007;5(2):209–14 Kennedy NA, Asser TL, Mountifield RE, Doogue MP, Andrews JM, Bampton PA. Thiopurine metabolite measurement leads to changes in management of inflammatory bowel disease. Intern Med J . 2013;43(3):278–86